Strategic Marketing Practices and Environmental Perception of Customer Oriented Service in Nigeria Deposit Money Banks in Lagos State - Onu Christopher A.; Adegbola E.A. (European Scientific Journal, ESJ, 2018)
This paper examines the nature and influence of the relationship between the bank’s strategic marketing practices and its service and seeks to determine the importance of strategic marketing practices in explaining the environmental perception of customers oriented service delivery. The study location was at the five selected Deposit Money Banks in Lagos State, Nigeria. A descriptive research design employing a stratified and convenience sampling techniques selected 74% of the bank staff which were contacted using questionnaires. The data collected were analyzed using the SPSS software version 19.0. Correlation analysis was conducted to establish the nature of the relationship between the bank’s strategic marketing practices and it customers oriented service delivery while regression analysis used to explain its influence on customers oriented service delivery. The finding showed that positive relationship exists between strategic marketing practices and customers oriented service delivery (r=0.749; Fcal=123.859; p<0.000). The researchers recommended that commercial banks should embrace strategic marketing by being focused to adapt to changes, marketing of assets and capabilities and marketing of innovation for the growth and survival of the industry.